Explorative case control study on the associations of serum vitamin D3, folic acid and vitamin B12 levels on Kawasaki disease and coronary artery lesions - Chen, Yanfei; Liu, Xingzhu; Li, Bin; Li, Jun; Meng, Lijuan; Ye, Caixia; Han, Linfei; Li, Hong; Deng, Li Li; Su, Zhongjian; Zhang, Xing (Frontiers in Nutrition, 2024)
Background: Kawasaki Disease (KD) is a pediatric vasculitic disorder characterized by systemic small vasculitis, notably coronary arteritis, with unclear pathogenesis. This explorative case-control study investigated the association between folic acid (FA), vitamin D3 (VD3), and vitamin B12 (VB12) levels and the different types of Kawasaki Disease, as well as the incidence of coronary artery lesions (CALs).. Methods: In this explorative case control study, 365 KD children admitted to our hospital from January 1, 2022 to June 30, 2023 were included as the KD group. Simultaneously, 365 healthy children who received physical examination during the same period were included as the control group. The KD group was divided into typical KD group and incomplete KD group (IKD group), CALs group and non-CALS group, and IVIG sensitive group and IVIG resistant group. The children with CALs were divided into small tumor group, medium tumor group and large tumor group. Serum levels of FA, VB12 and VD3 were compared across all groups. Results: Serum levels of FA and VD3 were significantly decreased in both the KD and CALs groups (P<0.05), and both factors were identified as independent risk factors for KD and CALs. Similarly, reduced serum VD3 levels were observed in the IKD and IVIG-resistant groups (P<0.05), with VD3 also being an independent risk factor for both IKD and IVIG resistance. Additionally, lower serum FA levels were noted in the group with large aneurysms (P<0.05), establishing FA as an independent risk factor for aneurysm size. Conclusion：Serum levels of folic FA and vitamin VD3 were significantly reduced in children with KD. Furthermore, these reductions were more pronounced in children with IKD and CALs. This pattern suggests that lower FA and VD3 levels may increase the risk of more severe coronary lesions in KD patients. Therefore, monitoring these biomarkers could provide valuable insights for early clinical diagnosis and intervention.